Cruise Passenger Satisfaction and the Role of Past Experience: Analysis of User-Generated Content - Medina, A.; Cardoso, M. G. M. S. (31sth Recent Advances in Retailing and Consumer Science Conference, 2025)
This study examines cruise passengers’ satisfaction based on user-generated content (i.e., quantitative ratings and narratives shared online). 416 text reviews and the corresponding ratings of quality attributes were collected from the Cruise Critic website for the cruise company with the highest market value and largest fleet worldwide, Royal Caribbean International. Within the used sample, 16 reviews were collected for each of Royal Caribbean's 26 ships. The relationships between cruisers’ Overall Satisfaction and quality attributes grounded in literature were investigated. Eight quality dimensions - ‘Entertainment’, ‘Dining’, ‘Fitness and Recreation’, ‘Cabins’, ‘Public Rooms’, ‘Value for Money’, ‘Embarkation’, and ‘Service’ - were tested and proved to affect overall satisfaction positively. ‘Value for Money’ stands out as having the most impact on Overall Satisfaction. Past Cruising Experience (scale: 1- first-time cruisers, 2-two to five previous cruises, 3- six to ten previous cruises, 4- more than ten cruises) was proved to negatively affect guests’ Overall Satisfaction, meaning that the higher the level of cruising experience, the lower the Overall Satisfaction tends to be, reflecting the high standards and expectations of the most experienced cruisers. Moderated Linear Regressions were used to analyze the moderator role of Past Experience in the relationships between each quality attribute and overall satisfaction. The moderating effects were found significant when regarding satisfaction with ‘Cabins’, ‘Public Rooms’, the ‘Embarkation’ process, and the ‘Service’ quality. The latter relationship was found to be the most sensitive to the moderating role of Past Experience. In general, the moderator effect tended to strengthen the direct relationship between the predictor and the Overall Satisfaction, as the level of experience decreased.